Introducing religion: religious studies for the twenty-first century - Ellwood, Robert S. (Routledge, 2025)
"Introducing Religion explores different ways of looking at religion in the twenty-first century. Providing a broad overview to the discipline of religious studies, this textbook introduces students to engaging and contemporary topics such as: sociology of religion, psychology of religion, history of religion, religion and art, religious ethics, popular religion, and religion and violence. Thoroughly updated throughout, this edition includes new coverage of current debates and hot topics in the field, such as concerns about 'essentialism' in religion, the importance of categorization, and the role of psychology in religious experience. This textbook is fundamental reading for students approaching this subject area for the first time"--